The Impact of the Emergency Disclosure on the Market Return and Stock Prices in the Damascus Stock Exchange Empirical Study in Damascus Stock Exchange (Journal of Hama University, 2020)
The research aims to identify the impact of the emergency disclosure on the market return and stock prices in the companies listed on the Damascus Securities Exchange. The research was conducted on companies listed on the Damascus Securities Market during the period 2014 - 2017. Many statistical tools and methods were used according to the SPSS program, in order to analyze the data and test the hypotheses. The results showed that the emergency disclosure does not affect the stock prices or the market return of the share. The most important recommendations were the need to raise awareness about the importance of emergency disclosure and the need to inform shareholders of the Substantial events occurring in the company